2015
DOI: 10.3390/ijerph13010025
|View full text |Cite
|
Sign up to set email alerts
|

Building Collaborative Health Promotion Partnerships: The Jackson Heart Study

Abstract: Building Collaborative Health Promotion Partnerships: The Jackson Heart Study. Background: Building a collaborative health promotion partnership that effectively employs principles of community-based participatory research (CBPR) involves many dimensions. To ensure that changes would be long-lasting, it is imperative that partnerships be configured to include groups of diverse community representatives who can develop a vision for long-term change. This project sought to enumerate processes used by the Jackson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
0
13
0
4
Order By: Relevance
“…Again, these findings are echoed by previous studies. A partnership evaluation found that commitment to long-term sustainability was one of five main recommendations [15]. Commitment to continued work past the end of the study was also one of the ten principles developed to guide health research with Indigenous Australian communities [33].…”
Section: Plan For Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Again, these findings are echoed by previous studies. A partnership evaluation found that commitment to long-term sustainability was one of five main recommendations [15]. Commitment to continued work past the end of the study was also one of the ten principles developed to guide health research with Indigenous Australian communities [33].…”
Section: Plan For Sustainabilitymentioning
confidence: 99%
“…Few research groups employing CEnR, community-based participatory research, community-academic partnerships, tribal-academic partnerships, and other forms of collaborative and participatory research have evaluated their own practices for success. Methodologies for evaluation include review through the Good Practice of Community Campus Partnerships framework [9]; review through the Contact, Initiation, Acceptance, Success, and Continuation Evaluation Framework [15]; analysis of meeting minutes and a group meeting [10]; analysis of program documentation, partner surveys, and meeting minutes [16]; and post-meeting evaluations [17]. The National Institute of Environmental Health Sciences' Partnerships for Environmental Public Health released an evaluation metrics manual to measure success in partnerships; the manual was based on academic and community partner input [18].…”
Section: Introductionmentioning
confidence: 99%
“…The CBPR is a community-based participatory research approach that involves a community's members, leaders, and academic researchers as equal participants [7]. In this manner, CBPR centers on the equality between participants and the fostering of a cooperative partnership for health promotion [8]. It is a method through which members can identify the on-site challenges themselves and produce ideas for solutions for their community that can be implemented more effectively regarding the validity and durability [9].…”
Section: Introductionmentioning
confidence: 99%
“…Um dos papéis da universidade inclui estimular a conscientização das comunidades locais sobre suas necessidades, bem como, auxiliar o trabalho em colaboração para atingir melhores resultados em estratégias de promoção à saúde 8 . O espaço universitário caracteriza-se por ser um ambiente dinâmico, interativo e marcado por um conjunto de ações previsíveis e imprevisíveis.…”
Section: Introductionunclassified